Could Zhou Xiaochuan Put Option Save Chinas Capital Market? - Shi, Kai; Nie, Li; Cai, Yifei; Wang, Yuan (Asian Economic and Financial Review, 2016)
This article proposes a new framework to analyze the impact of monetary policy on asset price. Based on the Sign-Restriction Approach proposed by Uhlig (2005) some orthogonal restrictions are imposed to filter out the interferences of money supply shock, easing monetary policy shock and national rescue shock on Zhou Xiaochuan Put Option shock in order to fully explore the effects of reserve requirement ratio (RRR) reduction and interest rate cut (so called “Double Down”) in China’s financial market system. It shows that Zhou Xiaochuan Put Option has faint but relatively enduring positive effects on share price, causing a slight RMB devaluation and a plunge of SHIBOR rate and treasury yields. Moreover, the impact on short-term financing cost and benefits is significantly larger than that on the long-term. In this rescue operation, Zhou Xiaochuan Put Option plays a certain role, but its effects are less vigorous than expected.